2009
DOI: 10.1016/j.neuron.2008.12.017
|View full text |Cite
|
Sign up to set email alerts
|

PDF Cells Are a GABA-Responsive Wake-Promoting Component of the Drosophila Sleep Circuit

Abstract: On page 800 of our paper, the intracellular solution used for measurements of LTP is erroneously described as containing KMeS0 3 . In reality, a cesium-based (CsMeSO 3 ) intracellular solution was actually used for these voltage-clamp recordings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Previous studies had suggested that this cell group is less important for circadian rhythms (Yang and Sehgal, 2001;Grima et al, 2004). However, recently, several groups demonstrated that the l-LN v cells are responsible for arousal/sleep (Sheeba et al, 2008a;Parisky et al, 2008;Shang et al, 2008). In addition, the l-LN v responds to light with increased spontaneous action potential firing (Sheeba et al, 2008b), and the ablation of the l-LN v cells reduces the diurnal photoresponse at dawn .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had suggested that this cell group is less important for circadian rhythms (Yang and Sehgal, 2001;Grima et al, 2004). However, recently, several groups demonstrated that the l-LN v cells are responsible for arousal/sleep (Sheeba et al, 2008a;Parisky et al, 2008;Shang et al, 2008). In addition, the l-LN v responds to light with increased spontaneous action potential firing (Sheeba et al, 2008b), and the ablation of the l-LN v cells reduces the diurnal photoresponse at dawn .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is very likely that in the cockroach, the light-dependent change in the length of the PDF-ir processes reflects respective light-dependent changes in the volume of PDF-ir neuropils. It is not completely resolved how light affects the PDF-ir l-LNvs to control PDF release at dawn in the fruit fly to elicit arousal (Parisky et al, 2008;Park and Griffith, 2006). Even less is known about the preand postsynaptic cells of the PDF-ir neurons in the cockroach.…”
Section: Plasticity Of the Optic Lobesmentioning
confidence: 99%
“…Here, we show that the response of the l-LNv clock neurons to GABA is also regulated by KCC and NKCC (Figure 3) 1 , suggesting that GABA polarity within these neurons changes during the day. The observation that the l-LNv receive GABAergic input 1,911 further support this idea. Because both KCC and NKCC are expressed in subsets of other clock neuronal groups (LNd, DN1, DN3) (Figure S1) it is likely that GABA polarity changes throughout the clock network in a daily fashion.…”
Section: Discussionmentioning
confidence: 57%
“…To determine if the behavioral effects of altered [Cl − ] i as a result of CCC modulation are reflected by physiological changes in the response to GABA, we performed patch-clamp recordings on the GABA responsive l-LNv neurons 1,911 to determine the GABA reversal potential (E GABA ). The l-LNv express the ionotropic chloride channel receptor GABA A 9 , and first, we confirmed KCC and NKCC expression in these neurons using suitable intragenic Gal4 insertions to drive a fluorescent cytoplasmic marker (Figure S1) 29 .…”
Section: Resultsmentioning
confidence: 99%